كفايات الوحدات التعليمية الرقمية لدي معلمي مرحلة التعليم الأساسي بمحلية كرري (Journal of Faculty of Education, 2021)
This study aims at investigation the sufficiency's digital Learning Objects (DLOs) among Basic Education's Teachers. The descriptive method was used, Population consists of Karary Basic education's teachers (4049). The Digital Learning Objects sufficiency questionnaire consists of 46 items among five factors: observe, select, collect, planning to used, and used, was used to collect the data. Chi square, t. test, and repeated one way ANOVA were used to analysis data. Result showed that the teacher beliefs the digital learning objects sufficiency's are necessary, there are differences in the digital learning objects sufficiency's for the select, and there are not differences at the digital learning objects sufficiency's due to gender. The study ended by rrecommendations and for future studies.The study aims to investigate the level of sufficiency of the Digital Learning Objects (DLO) model among Basic Education Teachers in Karari Locality. Population consists of 4049 teachers who are working in the schools in that Locality.A gigital Learning Ojects questionnaire was run among the teachers to measure the level of sufficiency. The questionnaire consisted of 46 items covering five major sufficiency factors, namely identification of learning units , their presentation and the design of plans to use them. The application of statistical methods methods such as Chai Squareand T-test showed that; although teachers are well aware of the importance of all sufficiency factors; differences exist in its application of the model as far as the process of selection is concerned.; no significant differences were identified due to gender differences. The paper recommends further studies in the issue of Digital Learning Objects Sufficiency because of its importance in controlling the learnig process
Keywords: كفايات وحدات التعلم الرقمية; محلية كرري; مرحلة التعليم الأساسي